Enhancing anti-tumor potential: low-intensity vibration suppresses osteosarcoma progression and augments MSCs' tumor-suppressive abilities - Xue Xiong; Qingji Huo; Kexin Li; Chang-peng Cui; Chunyi Chang; Charles Park; BonHeon Ku; Chin-Suk Hong; Hee-Chang Lim; Pankita H. Pandya; M. Reza Saadatzadeh; Khadijeh Bijangi‐Vishehsaraei; et al. (2024)
Rationale: Osteosarcoma (OS), a common malignant bone tumor, calls for the investigation of novel treatment strategies.Low-intensity vibration (LIV) presents itself as a promising option, given its potential to enhance bone health and decrease cancer susceptibility.This research delves into the effects of LIV on OS cells and mesenchymal stem cells (MSCs), with a primary focus on generating induced tumor-suppressing cells (iTSCs) and tumor-suppressive conditioned medium (CM).Methods: To ascertain the influence of vibration frequency, we employed numerical simulations and conducted experiments to determine the most effective LIV conditions.Subsequently, we generated iTSCs and CM through LIV exposure and assessed the impact of CM on OS cells.We also explored the underlying mechanisms of the tumor-suppressive effects of LIV-treated MSC CM, with a specific focus on vinculin (VCL).We employed cytokine array, RNA sequencing, and Western blot techniques to investigate alterations in cytokine profiles, transcriptomes, and tumor suppressor proteins.Results: Numerical simulations validated LIV frequencies within the 10-100 Hz range.LIV induced notable morphological changes in OS cells and MSCs, confirming its dual role in inhibiting OS cell progression and promoting MSC conversion into iTSCs.Upregulated VCL expression enhanced MSC responsiveness to LIV, significantly bolstering CM's efficacy.Notably, we identified tumor suppressor proteins in LIV-treated CM, including procollagen C endopeptidase enhancer (PCOLCE), histone H4 (H4), peptidylprolyl isomerase B (PPIB), and aldolase A (ALDOA).Consistently, cytokine levels decreased significantly in LIV-treated mouse femurs, and oncogenic transcript levels were downregulated in LIV-treated OS cells.Moreover, our study demonstrated that combining LIV-treated MSC CM with chemotherapy drugs yielded additive anti-tumor effects.Conclusions: LIV effectively impeded the progression of OS cells and facilitated the transformation of MSCs into iTSCs.Notably, iTSC-derived CM demonstrated robust anti-tumor properties and the Ivyspring International